2008
DOI: 10.1128/jcm.01018-08
|View full text |Cite
|
Sign up to set email alerts
|

Purulent Pericarditis with Greenish Pericardial Effusion Caused by Shewanella algae

Abstract: We report the first case of purulent pericarditis with greenish pericardial effusion caused by Shewanella algae in a patient with gastric and gallbladder cancer. This case expands the reported spectrum of infection caused by S. algae and raises the possibility that S. algae is a causative pathogen for purulent pericarditis. CASE REPORTA 76-year-old woman presented with fever and abdominal discomfort for 7 days. She had a history of gastric cancer, for which she had undergone radical gastrectomy, and gallbladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…However, rapid development of resistance to imipenem and piperacillin-tazobactam has been reported [1]. Thus the treatment options available are β-lactams (provided that the strain is susceptible), aminoglycosides, and quinolones [1,3,10]. Previous reports have shown that Shewanella infections should be treated aggressively with a combination of surgical therapy/debridement and appropriate antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rapid development of resistance to imipenem and piperacillin-tazobactam has been reported [1]. Thus the treatment options available are β-lactams (provided that the strain is susceptible), aminoglycosides, and quinolones [1,3,10]. Previous reports have shown that Shewanella infections should be treated aggressively with a combination of surgical therapy/debridement and appropriate antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Shewanella spp. have been implicated in skin and soft tissue infections, bacteraemia, biliary tract infections, thoracic empyema, endocarditis, dacryocystitis, intracranial abscess, arthritis, peritonitis, ventilator-associated pneumonia, and ear infections [2,3]. Shewanella algae and Shewanella putrefaciens are the two species of Shewanella that are most frequently implicated in human infections, although more than 80% are reportedly caused by S. algae [2].…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating 16S rRNA gene sequencing into the identification of Shewanella, more Shewanella species can be recognized as pathogenic organisms (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…They have attracted substantial interest for industrial applications, such as bioremediation of heavy metal contamination, generation of electrical power from biomass, and synthesis of -3 polyunsaturated fatty acids (1,2). More recently, Shewanella species have also been identified as opportunistic pathogens, typically from exposure of broken skin to the marine environment (3)(4)(5).…”
mentioning
confidence: 99%
“…LPS contains a hydrophobic lipid anchor known as lipid A, an inner core oligosaccharide, and a repeating O-antigen domain that is highly variable between species (6, 7). The sugar 3-deoxy-D-manno-octulosonic acid (Kdo) 3 is the first sugar added to lipid A, and laboratory strains of Escherichia coli cannot survive without synthesizing the minimal LPS substructure Kdo 2 -lipid A ( Fig. 1) unless compensatory mutations are introduced.…”
mentioning
confidence: 99%